Conformationally gated multisite proton-coupled electron transfer in the ribonucleotide reductase β subunit - Jiahua Deng; Sharon Hammes-Schiffer (Proceedings of the National Academy of Sciences, 2026)
Ribonucleotide reductase (RNR) is an essential enzyme that converts ribonucleotides into deoxyribonucleotides, enabling DNA synthesis and repair in all living organisms. Central to class Ia RNR activity is a long-range radical transport pathway spanning ∼ 32 Å across the α and β subunits by a series of proton-coupled electron transfer (PCET) reactions. Although the collinear PCET reactions in the α subunit have been extensively studied, the multisite, orthogonal PCET reactions in the β subunit are less well understood. This work focuses on orthogonal PCET between the redox-active tryptophan, W48, and interfacial tyrosine, Y356, in the β subunit. Multiscale modeling strategies are employed to explore this PCET reaction. The simulations show that radical transfer from W48 to Y356 is thermodynamically favorable and is likely to occur by electron transfer from Y356 to the W48 cationic radical in conjunction with proton transfer from Y356 to a glutamate, E52, which forms a hydrogen-bonding interaction with Y356 following oxidation of W48. The conformational gating motion of Y356 is shown to be critical for allowing this residue to participate in PCET with W48 in the β subunit and with a tyrosine in the α subunit. Application of vibronically nonadiabatic PCET theory highlights the significance of hydrogen tunneling and conformational motions that shorten the distance between Y356 and E52. This work demonstrates how conformational gating, hydrogen-bonding networks, and hydration at the α / β interface modulate PCET in RNR. These fundamental insights are also applicable to other biomolecular systems and may guide therapeutic and protein engineering applications.